Analysis of the Implementation of Citizenship Competence in the Civics Education Curriculum at the Junior High School Level in Bima Regency - Ruskialan, Ruskialan; Ahmad, Jamilah Binti; Suardi, Suardi; Syahrir, Musdalifah (Universitas of Muhammadiyah Makassar, 2025)
Citizenship education in Indonesia, particularly at the junior high school level, continues to face fundamental challenges, especially in terms of the comprehensive implementation of citizenship competencies within school curricula. These competencies encompass knowledge, skills, and attitudes that are essential for shaping responsible and active citizens who contribute meaningfully to national and civic life. This study aims to analyze the implementation of citizenship competencies within the educational unit curriculum through the subject of Pancasila and Civic Education (PPKn) at the junior high school level in Bima Regency. The research adopts a concurrent embedded mixed methods approach, integrating the strengths of both quantitative and qualitative data. Data were collected through observation, interviews, documentation, and the distribution of questionnaires to 210 students and several selected informants from two public junior high schools in Bima Regency. The study reveals that students’ knowledge and attitudinal aspects of citizenship are generally strong, particularly in their understanding of Pancasila values, citizens’ rights and obligations, and their appreciation of diversity. However, the skills dimension of citizenship such as critical thinking regarding human rights issues, understanding governmental systems, and applying civic values in both local and global contexts—still requires significant reinforcement. The study concludes that there is a pressing need for more contextual, practical, and project-based learning approaches to enhance students’ civic skills. The findings suggest that innovative and participatory teaching strategies in the implementation of the PPKn curriculum are crucial for cultivating active, tolerant, and responsible young citizens.